Development of a Range of Plausible Noncancer Toxicity Values for 2, 3, 7, 8-Tetrachlorodibenzo-p-Dioxin Based on Effects on Sperm Count: Application of Systematic Review Methods and Quantitative Integration of Dose Response Using Meta-Regression. (11th December 2020) - Wikoff, Daniele S; Urban, Jonathan D; Ring, Caroline; Britt, Janice; Fitch, Seneca; Budinsky, Robert; Haws, Laurie C
Abstract: Regulatory agencies have derived noncancer toxicity values for 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin based on reduced sperm counts relying on single studies from a large body of evidence. Techniques such as meta-regression allow for greater use of the available data while simultaneously providing important information regarding the uncertainty associated with the underlying evidence base when conducting risk assessments. The objective herein was to apply systematic review methods and meta-regression to characterize the dose-response relationship of gestational exposure and epididymal sperm count. Twenty-three publications (20 animal studies consisting of 29 separate rat experimental data sets, and 3 epidemiology studies) met inclusion criteria. Risk of bias evaluation was performed to critically appraise study validity. Low to very low confidence precluded use of available epidemiological data as candidate studies for dose-response due to inconsistencies across the evidence base, high risk of bias, and general lack of biological coherence, including lack of clinical relevance and dose-response concordance. Experimental animal studies, which were found to have higher confidence following the structured assessment of confidence (eg, controlled exposure, biological consistency), were used as the basis of a meta-regression. Multiple models were fit; points of departure were identified and converted to human equivalent doses. The resulting reference dose estimates ranged from approximately 4 to 70 pg/kg/day, depending on model, benchmark response level, and study validity integration approach. This range of reference doses can be used either qualitatively or quantitatively to enhance understanding of human health risk estimates for dioxin-like compounds.